The past, present and future of photonic glasses: A review in homage to the United Nations International Year of glass 2022. (April 2023) - Blanc, Wilfried; Gyu Choi, Yong; Zhang, Xianghua; Nalin, Marcelo; Richardson, Kathleen A.; Righini, Giancarlo C.; Ferrari, Maurizio; Jha, Animesh; Massera, Jonathan; Jiang, Shibin; Ballato, John; Petit, Laeticia
Abstract: Since the invention and further development of lasers in the 1960s, photonics has grown into a field that permeates virtually every aspect of modern life. As photonics deals with the generation, transmission, modulation, amplification, conversion, and detection of light, glasses have played crucial and central roles in a multitude of applications given glasses' diverse range of compositions, properties, and forms. They are also low-cost materials, recyclable and generally easy to fabricate. In homage to the United Nations International Year of Glass 2022, this paper reviews the past, present, and future of photonic glasses.